Distinct Expansion of Group II Introns During Evolution of Prokaryotes and Possible Factors Involved in Its Regulation - Miura, Masahiro C.; Nagata, Shohei; Tamaki, Satoshi; Tomita, Masaru; Kanai, Akio (Frontiers in Microbiology, 2022)
Group II introns (G2Is) are ribozymes that have retroelement characteristics in prokaryotes. Although G2Is are suggested to have been an important evolutionary factor in the prokaryote-to-eukaryote transition, comprehensive analyses of these introns among the tens of thousands of prokaryotic genomes currently available are still limited. Here, we developed a bioinformatic pipeline that systematically collects G2Is and applied it to prokaryotic genomes. We found that in bacteria, 25% (447 of 1,790) of the total representative genomes had an average of 5.3 G2Is, and in archaea, 9% (28 of 296) of the total representative genomes had an average of 3.0 G2Is. The greatest number of G2Is per genome was 101 in Arthrospira platensis (phylum Cyanobacteriota). A comprehensive sequence analysis of the intron-encoded protein (IEP) in each G2I sequence was conducted and resulted in the addition of three new IEP classes (U1–U3) to the previous classification. This analysis suggested that about 30% of all IEPs are noncanonical IEPs. The number of G2Is per genome was defined almost at the phylum level, and at least in the following two phyla, Firmicutes and Cyanobacteriota, the type of IEP was largely associated as a factor in the G2I increase, i.e., there was an explosive increase in G2Is with bacterial C-type IEPs, mainly in the phylum Firmicutes, and in G2Is with CL-type IEPs, mainly in the phylum Cyanobacteriota. We also systematically analyzed the relationship between genomic signatures and the mechanism of these increases in G2Is. This is the first study to systematically characterize G2Is in the prokaryotic phylogenies.